Morphology, thermal, and mechanical behavior of ethylene octene copolymer toughened polyamide 6/polypropylene nanocomposites - Wahit, Mat Uzir (SAGE Publications, 2006)

(untitled)
Polyamide 6/polypropylene (PA6/PP = 70/30 parts) blends containing 10 wt% of ethylene octene copolymer (POE) and different loading (2-6 wt%) of organophilic modified monmorillonite (MMT, organocaly) are prepared using a twin screw extruder followed by injection molding. Polypropylene grafted maleic anhydride (PP-g-MAH) of 5 wt% is also incorporated as a compatibilizer. The mechanical properties of blended nanocomposites are studied through tensile, flexural, and impact tests. The morphology, essentially comprised of PP and POE particles dispersed in the PA6 matrix, is characterized by scanning electron microscopy (SEM). Wide angle X-ray diffraction (XRD) is used to characterize the formation of nanocomposites. The thermal properties are characterized by using differential scanning calorimeter (DSC) and thermogravimetry analysis (TGA). The dynamic mechanical properties of the PA6/PP blend and PA6/PP/POE nanocomposites are analyzed by using a dynamic mechanical thermal analyzer (DMTA). The incorporation of organoclay does not influence the melting temperature or crystallinity of PA6 or PP. However, the thermal stability of the nanocomposites improved by about 20 C with the incorporation of 2-4 wt% organoclay. The PA6/PP nanocomposites containing 4 wt% of organoclay and 10 wt% of POE exhibit good toughness retention without significant loss of stiffness and strength properties.